Enfermagem e o gerenciamento de custos: revisão sistemática nacional e internacional - Teixeira, Alessandra Martiniak [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Objectives: conduct a systematic review of national and international literature, to classify the types of production, comparing the two literatures and synthesize knowledge in the area. Method: Systematic Review of Literature, in the databases LILACS, CINAHL and MEDLINE for selection of articles in their entirety, the data extracted from the articles selected were: the study of bibliographic information (title, author, journal, place of study and year of publication), and general information (multidisciplinary production or specific area, language, type of study, type of population and contributions of the study). The categories established for classification of publications were: raising the cost of procedures/ interventions, economic evaluation of specific intervention, inclusion of nursing in the economic context, using cost as an important variable in the study. Results: The study included 39 publications, with 31% of national production and the remaining 69%, internationally. Most publications were classified according to category of economic evaluation of specific intervention, followed by the category of raising the cost of procedure / intervention, which fits the majority of national production. Human resources is shaped as an important variable for obtaining cost studies that proposed to make this calculation. Conclusion: The production of literature in nursing cost management is relevant in number of publications within the proposed period and is directed to different areas within this theme. There are significant differences in national and international literature: these last use more accurate methods, have more content theorized, use more the economic evaluation tools and related more costs with a amplified context. The production of such knowledge should continue as far as possible and putting that knowledge relating the current reality, in order to amplify the field of nursing and add value

Objetivos: realizar uma revisão sistemática de literatura nacional e internacional, classificar os tipos de produção, comparar as duas literaturas e sintetizar o conhecimento na área. Método: Revisão Sistemática de Literatura, nas bases de dados LILACS, CINAHL e MEDLINE para seleção de artigos na íntegra, os dados extraídos dos artigos selecionados foram: informações bibliográficas do estudo (título, autores, periódico, local do estudo e ano de publicação), e informações gerais (produção multidisciplinar ou de área especifica, idioma, tipo de estudo, tipo de população e contribuições do estudo). As categorias estabelecidas para classificação das publicações foram: levantamento de custo de procedimento/intervenção, avaliação econômica de determinada intervenção, inserção da enfermagem no contexto econômico, utilização de custos como uma variável importante do estudo. Resultados: foram analisados 39 publicações, sendo 31% de produção nacional e o restante 69% internacional. A maioria das publicações foi classificada segundo a categoria de avaliação econômica de determinada intervenção, seguida da categoria de levantamento de custo de procedimento/intervenção, na qual se enquadra a maioria da produção nacional. Os recursos humanos se configuraram como variável importante para obtenção de custos nos estudos que se propuseram a fazer este calculo. Conclusão: a produção de literatura da enfermagem em gerenciamento de custos é relevante em número de publicações dentro do período proposto e é direcionada para diferentes campos dentro desse tema. Há diferenças significativas na literatura nacional e internacional: estas ultimas utilizam metodologias mais apuradas, apresentam conteúdo mais teorizado, utilizam mais os instrumentos de uma avaliação econômica e relacionam mais os custos com um contexto amplificado... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Enfermagem; Analise de valor (Controle de custo)